Increasing Knowledge About Stunting and Growth Charts Through Seminars and Assistance for Parents of Students Aged 3 – 18 Years - Liman, Patricia Budihartanti; Dita Setiati; Yuliana; Faradilla, Meutia Atika; Anastasya, Karina Shasri; Yenny (Universitas Pendidikan Ganesha, 2024)
Stunting and obesity in Indonesia are still unresolved problems This may be caused by a lack of parental knowledge. StResearch regarding increasing parental knowledge about stunting and the use of growth charts is still controversial. This research aims to determine the effectiveness of health education on parental knowledge. This was a one-group experimental pre- and post-test study involving 61 parents of children aged 3-18 years. A modified structured questionnaire was used to assess stunting knowledge scores through seminars and growth chart knowledge scores through mentoring. Data were analyzed using SPSS ver. 29.0.2.0. The Mann-Whitney test was used to compare changes in scores after the seminar and mentoring training. Post-test knowledge score of seminars and mentoring method improved significantly compared with pretest scores (p < 0.001 for both analyses). The increase in scores for the mentoring method was three times compared to the seminar method (p=0.016). The implication of these findings is that mentoring methods can be considered further on a larger community scale for parent capacity building programs to achieve reduction of malnutrition in Indonesia.